2021
DOI: 10.12703/r/10-1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the understanding and management of liposarcoma

Abstract: Liposarcomas are a common subfamily of soft tissue sarcoma with several subtypes recognized by the World Health Organization: atypical lipomatous tumors (ALT)/well-differentiated liposarcoma (WDLPS), dedifferentiated liposarcoma (DDLPS), myxoid liposarcoma (MLPS), pleomorphic liposarcoma (PLPS), and myxoid pleomorphic liposarcoma (MPLPS). Despite shared adipocytic features among liposarcomas, the clinical approach to each subtype differs based on histology, location, clinical behavior, and specific oncogenic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 72 publications
0
32
0
3
Order By: Relevance
“…Immunohistochemistry tests for desmin, vimentin, α -SMA, CK, leukocyte common antigen (LCA), CD34, human melanoma black 45 (HMB45), epithelial membrane antigen (EMA), and S100 should be analyzed in sarcomas to rule out another type of tumors (non-mesenchymal malignant tumors or sarcomas with a specific line of differentiation) [ 4 ]. MDM2 gene amplification analysis represents the standard differential diagnosis of ALT/WDLPS and DDLPS [ 25 , 26 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Immunohistochemistry tests for desmin, vimentin, α -SMA, CK, leukocyte common antigen (LCA), CD34, human melanoma black 45 (HMB45), epithelial membrane antigen (EMA), and S100 should be analyzed in sarcomas to rule out another type of tumors (non-mesenchymal malignant tumors or sarcomas with a specific line of differentiation) [ 4 ]. MDM2 gene amplification analysis represents the standard differential diagnosis of ALT/WDLPS and DDLPS [ 25 , 26 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…DDLS has poor sensitivity to chemotherapy. Anthracyclinebased therapy is the first line, either as monotherapy or in combination with ifosfamide [13,14]. Response rates to systemic therapy are reported to be 12% in WDLS/DDLS, with median overall survival of 15 months [13].…”
Section: Discussionmentioning
confidence: 99%
“…Response rates to systemic therapy are reported to be 12% in WDLS/DDLS, with median overall survival of 15 months [13]. Novel targeted-therapies are emerging with inhibitors of CDK4/6, MDM2, Exportin-1, PI3K, mTOR, and tyrosine kinase [13,14]. The role for these therapies remains under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…DDLPS is a highly malignant sarcoma with an unfavorable prognosis. Although systemic chemotherapy is recommended for unresectable or metastatic cases, conventional chemotherapy has no overall survival benefit [13]. Preclinical studies using patient-derived cell lines are essential for the development of novel treatment methods.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the distant metastasis rate is as high as 15-30%, resulting in an overall mortality rate of 28% [5]. Systemic chemotherapy is considered in unresectable or metastatic cases, but DDLPS is known to be insensitive to conventional chemotherapy [13,14]. Although a recent retrospective study reported the efficacy of conventional chemotherapy on DDLPS by assessing a vascular response in addition to responsive evaluation criteria in solid tumor (RECIST), the effect on overall survival has not been well clarified [15].…”
Section: Introductionmentioning
confidence: 99%